Alcoviteira e misoginia na literatura ocidental: contribuições ao teatro de Gil Vicente - Pires, Leicina Alves Xavier (2023)
The main goal of this thesis is to prove that Gil Vicente, even offering a prominent role to the female sex, wove a misogynist speech around him, mainly of the procuress social type. In this work, we adopt the initial hypothesis that Gil Vicente self reflected in the character Celestina, from the plot La Celestina, by Fernando Rojas, published around 1499/1500, and, from her, created derivations of this social type, through which we demonstrate the presence of misogynistic discourse. Thus, we profiled six procuresses, present in different farces: Geneva Pereira, in Auto das Fadas (1511? 1527?); Branca Gil, in O Velho da Horta (1512); Brísida Vaz, in Auto da Barca do Inferno (1517); old Beata, in Rubena's Comedy (1521); Lianor Vaz, in Farsa by Inês Pereira (1523), and Ana Dias, in Juiz da Beira (1525).It is intended, therefore, to demonstrate that these characters, laughable and farcical, appear to be independent and revolutionary, however, most of the time, they end up being judged and punished in some way, as Celestina had been, highlighting the vilification of the female sex, which had its beginnings in the ancient period and was consolidated in the medieval period.